2014
DOI: 10.1002/asi.23172
|View full text |Cite
|
Sign up to set email alerts
|

“The sum of all human knowledge”: A systematic review of scholarly research on the content ofWikipedia

Abstract: Wikipedia might possibly be the best-developed attempt thus far of the enduring quest to gather all human knowledge in one place. Its accomplishments in this regard have made it an irresistible point of inquiry for researchers from various fields of knowledge. A decade of research has thrown light on many aspects of the Wikipedia community, its processes, and content. However, due to the variety of the fields inquiring about Wikipedia and the limited synthesis of the extensive research, there is little consens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(134 citation statements)
references
References 96 publications
(125 reference statements)
0
124
0
10
Order By: Relevance
“…It is often said that Wikipedia only works in practice; in theory, it should never work. Computational social scientists have elucidated many of the reasons why the crowdsourcing model Wikipedia works [64], and thus could effectively contribute to a better understanding of the problem of digital misinformation. …”
Section: Discussionmentioning
confidence: 99%
“…It is often said that Wikipedia only works in practice; in theory, it should never work. Computational social scientists have elucidated many of the reasons why the crowdsourcing model Wikipedia works [64], and thus could effectively contribute to a better understanding of the problem of digital misinformation. …”
Section: Discussionmentioning
confidence: 99%
“…Concluiu que a melhor das quatro foi a Wikipédia em inglês, seguida da Enciclopédia Nacional Dinamarquesa, da Encyclopedia Britannica e da Wikipédia em dinamarquês. Mesgari et al (2015) revisaram sistematicamente 110 artigos sobre o conteúdo da Wikipédia. Identificaram duas correntes principais de pesquisa: sobre a qualidade do conteúdo (incluindo abrangência, atualidade, legibilidade e confiabilidade) e sobre seu tamanho.…”
Section: Wikipedia As Reference Source: Assessment and Prospects 1 Inunclassified
“…They found that the biggest repositories contain no more than several hundreds of thousands of objects, and they located only two repositories with more than one hundred thousand users (e.g., Curriki and Merlot). This contrasts Little repositories such as Wikipedia, which contains more than 26 million articles in more than 250 languages and serves more than 500 million readers each month (Mesgari, Okoli, Mehdi, Nielsen, & Lanamäki, 2015). (Murphy, Hashim, & O'Connor, 2007); Connexions is an Internet repository containing educational content focusing on books, organized in modules that include tools for editing and reorganizing content (Burrus, 2014); MIT OpenCourseWare is a repository containing the academic content of entire courses from all the MIT university faculties, where some of the courses even include full video lectures (d 'Oliveira, Carson, James, & Lazarus, 2010).…”
Section: Introductionmentioning
confidence: 97%